2020
DOI: 10.1371/journal.pone.0230380
|View full text |Cite
|
Sign up to set email alerts
|

α-parvin is required for epidermal morphogenesis, hair follicle development and basal keratinocyte polarity

Abstract: Epidermal morphogenesis and hair follicle (HF) development depend on the ability of keratinocytes to adhere to the basement membrane (BM) and migrate along the extracellular matrix. Integrins are cell-matrix receptors that control keratinocyte adhesion and migration, and are recognized as major regulators of epidermal homeostasis. How integrins regulate the behavior of keratinocytes during epidermal morphogenesis remains insufficiently understood. Here, we show that α-parvin (α-pv), a focal adhesion protein th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…This switch of IAC classes functionally translated into impaired cellular adhesion, indicating a defect in efficient mechanical linkage between IACs and the cytoskeleton (Figure 7). Although prior studies have observed that the sole deletion of PARVA already resulted in impaired cellular adhesion, altered cytoskeletal architecture, and adhesion site formation, 32 , 63 compensatory upregulation of PARVB in podocytes largely prevented any overt cellular dysfunction. In fact, a counterbalancing regulation of Parvin proteins has been previously demonstrated 70 …”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This switch of IAC classes functionally translated into impaired cellular adhesion, indicating a defect in efficient mechanical linkage between IACs and the cytoskeleton (Figure 7). Although prior studies have observed that the sole deletion of PARVA already resulted in impaired cellular adhesion, altered cytoskeletal architecture, and adhesion site formation, 32 , 63 compensatory upregulation of PARVB in podocytes largely prevented any overt cellular dysfunction. In fact, a counterbalancing regulation of Parvin proteins has been previously demonstrated 70 …”
Section: Discussionmentioning
confidence: 78%
“…To test the relevance of PARVA in podocytes, we used a recently established conditional allele for Parva 32 , 63 . We crossed the podocyte-specific hNPHS2-Cre line with a floxed allele for Parva and validated KO efficiency in situ (Figure 2, A and B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have revealed that adhesion signals are important factors in HF and AGA development. For example, α-parvin, which is a FA protein that couples integrins to actin cytoskeleton, is indispensable to HF development (Altstaetter et al, 2020 ). Furthermore, there is cross-talk between FA/integrin and Wnt signaling pathways, which is one of the most important signaling pathways in AGA (Ridgway et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that adhesion signals are important factors in HF and AGA development. For example, α-parvin, which is a FA protein that couples integrins to actin cytoskeleton, is indispensable to HF development (Altstaetter et al, 2020). Furthermore, there is cross-talk between FA/integrin and Wnt signaling pathways, which is one of the most important signaling pathways in AGA (Ridgway et al, 2012).…”
Section: Discussionmentioning
confidence: 99%